2023
DOI: 10.1039/d2ra08006k
|View full text |Cite
|
Sign up to set email alerts
|

Identifying novel selective PPO inhibitors through structure-based virtual screening and bio-evaluation

Abstract: The PPO inhibitor ZINC70338 obtained from a docking based virtual screening has a certain selectivity for Nicotiana tabacum PPO and human PPO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The radii of gyration (ROG) indicates how the atoms are distributed in a particular axis, and serves as a measure of the proximity between molecules. 19 As shown in Figure 8(C) , the radius of gyration of the complex in the ZDS20 -PD-L1 system is lower than that of BMS202 , indicating that ZDS20 makes the complex system compact and stable. Additionally, the solvent accessible surface area (SASA) of a protein is widely recognised as a critical determinant in protein folding and stability investigations.…”
Section: Resultsmentioning
confidence: 90%
“…The radii of gyration (ROG) indicates how the atoms are distributed in a particular axis, and serves as a measure of the proximity between molecules. 19 As shown in Figure 8(C) , the radius of gyration of the complex in the ZDS20 -PD-L1 system is lower than that of BMS202 , indicating that ZDS20 makes the complex system compact and stable. Additionally, the solvent accessible surface area (SASA) of a protein is widely recognised as a critical determinant in protein folding and stability investigations.…”
Section: Resultsmentioning
confidence: 90%
“…33 The TIP3PBOX(Buffer ≥10.0 Å) waters model was used to dissolve the solute in an uncapped periodic box of a solvent wall distance from 1.2 nm, and then sodium and chloride ions were added to keep the system electrically neutral. 34…”
Section: Methodsmentioning
confidence: 99%
“…64,71 In addition, several of the existing PPO inhibitors exhibit low biological selectivity and have certain impacts on nontarget organisms. 72 It has been reported that the plant toxicity of acifluorfen was caused by alterations in aromatic amino acid metabolism and phenylpropanoid biosynthesis. 73 The carboxyl group on the DPE molecule has frequently been modified in order to search for novel PPO inhibiting herbicides.…”
Section: Synthetic Carboxylic Acids and Their Derivatives For Herbici...mentioning
confidence: 99%
“…The success in acifluorfen has attracted attention to the combination of the 2-Cl-4-CF 3 phenyl group with the 4-NO 2 phenyl group for the PPO inhibition herbicide investigation. A number of highly efficient DPE-typed herbicides have been developed based on the structure of acifluorfen through the introduction of additional ester or amide groups on the 3-position of the B ring (Figure b). , However, certain disadvantages such as resistance in several weeds have made it necessary and urgent to develop novel structures in PPO inhibitors. , In addition, several of the existing PPO inhibitors exhibit low biological selectivity and have certain impacts on nontarget organisms . It has been reported that the plant toxicity of acifluorfen was caused by alterations in aromatic amino acid metabolism and phenylpropanoid biosynthesis …”
Section: Synthetic Carboxylic Acids and Their Derivatives For Herbici...mentioning
confidence: 99%